(untitled) (Contemporary Mathematics, 2024)
This paper deals with the effects of magnetic fields on unsteady Casson blood fluid flow in a stenosis artery. The effects of thermo-diffusion, thermal radiation, metabolic heat sources, and heat absorption are also considered. The flow is confined by the oscillating pressure gradient. The governing equations are remodeled into a system of PDEs in cylindrical form, which is then converted to dimensionless form using the similarity transformation. A definition of the Caputo-Fabrizio fractional order derivative is applied to the governing dimensionless form. The Laplace transform and the finite Hankel transform are used to obtain the analytic results. From the graphical results, it is illustrated that the external magnet reduced the rate of blood flow. It is also deduced that radiation tends to improve the rate of heat transfer, whereas the thermo-diffusion parameter tends to reduce the mass transfer process.